Branched-Chain Amino Acids (BCAAs) - oral supplementation and its effects in resistance training and treatment - Bieńkowski, Borys; Feja, Krzysztof; Łuczak, Ewa; Jachowicz, Krzysztof; Petryla, Piotr; Suwała, Zuzanna; Marchewka, Urszula; Ostafin, Kamil; Rektor, Natalia; Edyko, Krzysztof (Journal of Education, Health and Sport, 2023)
Introduction: Branched - chain amino acids (BCAAs) are essential components of proteins that play a crucial role in regulating numerous physiological processes in the human body. This article provides a comprehensive analysis of scientific research on BCAAs, including their involvement in metabolism, protein biosynthesis, and the regulation of anabolic processes. We reviewed the supplementation of BCAAs and its impact on sports performance, body composition, and the therapeutic applications of BCAAs Materials and methods: This study is based on medical articles collected from the PubMed database spanning the years 2011-2023. The research was conducted through the analysis of keywords such as "BCAA supplementation", "BCAA metabolism", and "BCAA treatment". Results: The physiology of BCAAs is well understood. The use of oral supplements containing BCAAs does not have a positive impact on muscle hypertrophy, muscle strength, and post-workout muscle soreness in resistance training. However, branched chain amino acids may serve as a safe and effective therapeutic approach in the treatment of liver cirrhosis.